Electrophysiological Analysis of Synaptic Transmission in Drosophila - Bykhovskaia, Maria (Wiley Interdiscip Rev Dev Biol, 2017)
Synaptic transmission is dynamic, plastic, and highly regulated. Drosophila is an advantageous model system for genetic and molecular studies of presynaptic and postsynaptic mechanisms and plasticity. Electrical recordings of synaptic responses represent a wide-spread approach to study neuronal signalling and synaptic transmission. We discuss experimental techniques that allow monitoring synaptic transmission in Drosophila neuromuscular and central systems. Recordings of synaptic potentials or currents at the larval neuromuscular junction (NMJ) are most common and provide numerous technical advantages due to robustness of the preparation, large and identifiable muscles, and synaptic boutons which can be readily visualized. In particular, focal macropatch recordings combined with the analysis of neurosecretory quanta enable rigorous quantification of the magnitude and kinetics of transmitter release. Patch-clamp recordings of synaptic transmission from the embryonic NMJ enable overcoming the problem of lethality in mutant lines. Recordings from the adult NMJ proved instrumental in the studies of temperature-sensitive paralytic mutants. Genetic studies of behavioural learning in Drosophila compel an investigation of synaptic transmission in the central nervous system (CNS), including primary cultured neurons and an intact brain. Cholinergic and GABAergic synaptic transmission has been recorded from the Drosophila CNS both in vitro and in vivo. In vivo patch-clamp recordings of synaptic transmission from the neurons in the olfactory pathway is a very powerful approach, which has a potential to elucidate how synaptic transmission is associated with behavioural learning.